Beliefs, attitudes, and reflections of EFL pre-service teachers while exploring critical literacy theories to prepare and implement critical lessons - Gutiérrez, Claudia Patricia (Colombian Applied Linguistics Journal, 2015)
Foreign language teaching and learning is an issue of high relevance nowadays in Colombia. Unfortunately, language teaching has often been reduced to the mastery of language structures, disregarding the vast number of possibilities that language teaching provides to involve students in the discussion and analysis of issues that affect their everyday life. Shifting language teaching toward this goal, however, has to be emphasized more in language teacher preparation programs. To gain a better understanding of the implication of this shift, this study explored the beliefs, attitudes, and reflections of three student-teachers from a foreign language teaching program at a public university towards the exploration of Critical Literacy theories, and the design and implementation of critical lessons. In this exploratory case study, data collected included audio-recordings of class discussions and individual interviews with the three participants, their reflections during different stages, and class observations of their lesson implementation. Results from this study suggest that exposing future EFL teachers to Critical Literacy approaches to language teaching can have various effects on their perspectives towards education and their teaching practice. Thus, those effects might be influenced by factors such as their teaching experience, their backgrounds, and their prior beliefs.